Illuminance Sensing in Agriculture Applications Based on Infra-Red Short-Range Compact Transmitter Using 0.35 $\mu{\text{m}}$ CMOS Active Device - Roman Sotner; Jan Jerabek; Ladislav Polak; Jiri Petrzela; Winai Jaikla; Sunti Tuntrakool (My University, 2020)
This paper introduces a novel electronic system for simplex low-bitrate infra-red (IR) communication applications. The transmitter is implemented completely by analog building blocks, formed with the help of a recently fabricated chip that includes active elements allowing various modular interconnections. For the design of this chip, the ON Semiconductor C035 0.35μm I3T25 technology was chosen due to the trade-off between cost, efficiency and obtainable parameters. The designed transmitter operates as a voltageto-duty cycle converter, using pulse width modulation that causes ON/OFF keying of the carrier signal for infra-red (IR) diode. The duty cycle variable between 7% and 83% is modulated by the input voltage (in the range of ±0.8 V) of the transmitter. The use case of the proposed concept in the measurement of illuminance within the range of 30 lx and 550 lx is also presented. The quality of the transmission was evaluated as the error between the transmitted and received values of the duty cycle (kept mostly below 10 %). The maximal power consumption of the transmitter reaches 180 mW.
Keywords: Optical Wireless Communication Technologies